2004
DOI: 10.1080/01431160412331269670
|View full text |Cite
|
Sign up to set email alerts
|

ENVISAT multisensor data for fire monitoring and impact assessment

Abstract: The European ENVISAT satellite provides both optical and radar measurements of the Earth's surface. In this Letter, three ENVISAT instruments were used to investigate the extent and impact of the forest and peatland fires that devastated large areas in Central Kalimantan, Indonesia in 2002. Reduced spatial resolution MERIS imagery was used to identify simple land cover features and smoke plumes. Fire hotspots were detected by band 3.7 mm of Advanced Along Track Scanning Radiometer (AATSR) night-time acquisitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…Moreover, research on forest fires in boreal forests has shown that the backscatter intensity from burned scars is stronger than that from unburned areas due to changes in moisture content [11,12,[15][16][17]. Siegert and Ruecker [18] and Huang and Siegert [19] made similar observations in a tropical rain forest environment, but found that fires caused a decrease in backscatter under dry weather conditions whereas under wet conditions burned areas could not be discriminated from unburned areas.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Moreover, research on forest fires in boreal forests has shown that the backscatter intensity from burned scars is stronger than that from unburned areas due to changes in moisture content [11,12,[15][16][17]. Siegert and Ruecker [18] and Huang and Siegert [19] made similar observations in a tropical rain forest environment, but found that fires caused a decrease in backscatter under dry weather conditions whereas under wet conditions burned areas could not be discriminated from unburned areas.…”
Section: Introductionsupporting
confidence: 56%
“…The same conclusion could not be drawn for forested areas as approximately 70% of the omitted areas showed values higher than 0.5 degrees of dNDMI. In this case, the influence of local incidence angle might have caused the misclassifications since studies have shown that the backscatter coefficient of burned areas varies as a function of the incidence angle [19,52]. It was observed that 40% of the omitted burned forest was located in areas with local incidence angles ≤25° and ≥50°.…”
Section: Classification Resultsmentioning
confidence: 99%
“…However, while the detection of natural or technological fires using satellite images has been given much attention and is now performed on a routine basis (Cahoon et al, 1994;Christopher et al, 1996;Chrysoulakis & Cartalis, 2000, 2003bHuang & Siegert, 2005;Kaufman et al, 1990;Prins et al, 1998;Pu et al, 2004), fewer interest has been given to automatic plumes detection. Methods have been developed for plume detection based either on image photointerpretation using pseudocoloured compositions of Advance Very High Resolution Radiometer (AVHRR) spectral channels (Chung & Le, 1984;Kaufman et al, 1990;Randriambelo et al, 1998), or on retrieving of optical depth of heavy aerosol plumes (Wong & Li, 2002), or on multi-threshold methods based on spectral indices (Baum & Trepte, 1999;Chrysoulakis & Cartalis, 2003a;Chrysoulakis et al, 2005) and textural features (Christopher & Chou, 1997;Christopher et al, 1996), or on multi-threshold methods based on neural networks (Li et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The type of plume information that can be derived from satellite data includes location, timing and areal extent measurement, and to a certain extent a measure of the amount of aerosols and some types of trace gases released Penner et al, 1992). In several past studies, satellite data have been used to quantify the gaseous output from fires (Cahoon et al, 1994;Chrysoulakis & Cartalis, 2003a;Chrysoulakis & Opie, 2004;Chung, 2002;Dousset et al, 1993;Feingold et al, 2001;Ferrare et al, 1990;Huang & Siegert, 2005;Kaufman & Fraser, 1997;Kaufman et al, 1992;Khazenie & Richardson, 1993;Randriambelo et al, 1998;Rudich et al, 2003). Other studies examined the effects of large plumes on clouds (Feingold et al, 2001;Kaufman & Fraser, 1997;Kaufman & Nakajima, 1993;Rosenfeld, 1999;Rosenfeld & Lensky, 1998;Rudich et al, 2003) and the feasibility of using satellite images to detect largescale pollution episodes (Cahoon et al, 1994;Chung & Le, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…MERIS was mainly designed for ocean colour applications, as it provides high spectral resolution in the range of the blue to the near infrared regions (Gower and Borstad 2004). The application of MERIS data to fire applications is scarce: identification of smoke plumes (Huang and Siegert 2004), discrimination of burn severity (De Santis and Chuvieco 2007;Roldan-Zamarron, Merino-De-Miguel et al 2006). Mapping BA with MERIS has only been performed at regional level (Oliva, Martin et al 2011) using different vegetation indices while (González-Alonso 2009) combined fire hotspots from MODIS and NIR reflectance values from MODIS and MERIS imagery.…”
Section: Introductionmentioning
confidence: 99%